L-Arginine effectively alleviates doxorubicin-induced cardiac dysfunction by inhibiting myocardial fibrosis - Mo-li Zhu; Rui Hao; Meng-yao Zhao; Pei-yao Liu; Hong-dou Zhang; Peng Li; Ya-ling Yin; Hui-jun Liu; Guang-qiu Ren; Jie Zhang; Jing Yang (Molecular Biology Reports, 2026)

Identification of novel loci regulating circulating melatonin and its causal relationship with hypertension - Lin Yan; Yang Qiu; Zhiwen Mo; Mingli Li; Xueran Huang; Yongfen Gao; Boteng Yan; Qiantu Hu; Haiying Zhang; Zengnan Mo; Rui Lin (Human Genetics, 2026)

Leveraging yeast as cell factories to empower next generation food innovation - Zifan Dou; Jingyao Zhu; Ruyi Song; Ruixue Liu; Haonan Huang; Xinna Qiu; Shuo Ren; Demei Meng; Yuyu Zhang; Rui Yang (Trends in Food Science & Technology, 2026)

Ball-milled submicron natural pyrite particles for efficient peroxysulphate activation and monochlorobenzene degradation: The role of low-molecular-weight organic acids and reduced sulfur species driving iron redox cycles - Shaofei Wen; Rui Qiu; Zhenyu Ding; Shaoping Kuang; Hongwen Sun; Peng Zhang (Journal of Environmental Chemical Engineering, 2026)

Evaluation and forecasting of habitat suitability and thermal growth responses in the mud clam Geloina coaxans under climate change - Bing-Xian Liu; Yu-Yang Zhang; Cheng-Rui Yan; Zhan-Wei Zhao; Ning Zhang; Lin-Xuan Ma; Xian-Bo Qiu; Yun-Wei Dong (Marine Environmental Research, 2026)

Construction of Brick-Wall-Like Topological Olefin-Linked Covalent Organic Frameworks via a Steric-Hindrance-Mediated Strategy for Efficient Uranium Capture - Cheng-Peng Niu; Rui Zhang; Zhi-Hai Peng; Zhen-Wen Zhang; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2026)

Adaptive genetic trade-offs govern the enantioselective degradation and horizontal transfer of ibuprofen catabolic genes - Weihao Zhu; Mingli Jiang; Rui Fan; Kaihua Pan; Shenghao Wang; Lu Huang; Qiantong Ru; Yinhu Jiang; Qian Li; Qian Zhu; Mingliang Zhang; Zhijian Ke; et al. (Journal of Hazardous Materials, 2026)

Triterpenoid saponin variation in cultivated and mountain-cultivated ginseng aqueous extracts is associated with distinct myocardial multi-omics and intestinal microbial–metabolic response patterns - Yanxu Zhang; Runlai Lu; Rui Liu; Ye Qiu; Yifei Wang; Jialin Wei; Qiang Chen; Chunping Xiao; Zhidong Qiu (Food Research International, 2026)

Carbon quota redistribution and subsidy incentives for China's provinces: Balancing efficiency and regional equity - Xiao Lei; Chenyang Hu; Rui Qiu; Bin Zhang (Environmental Impact Assessment Review, 2026)

An energy-spectrum-biased auto-importance sampling method for variance reduction in Monte Carlo energy spectrum simulations - Yang Zhou; Hui Zhang; Zhen Wu; Yisheng Hao; Rui Qiu; Jiajun Wu; Jiahe Shang; Junli Li (Annals of Nuclear Energy, 2026)

Different drivers of active and inert carbon fraction on forest soil aggregate stability: a functional partitioning approach - Jing Lin; Rui Wang; Miao Xia; Jian-cong Zhang; Peng Qiu; Ke-xin Zhang; Bo Chang; Yu-lin Zhang; Tian-zi Xie; Yi Jian; Jia-yuan Wang; Shan-shan Guo (Journal of Soils and Sediments, 2026)

Asymmetric atmospheric secondary circulation response to a sea surface submesoscale cold filament - Jun Yang; Ziqi Zhang; Jen-Ping Peng; Dongxiao Wang; Chunhua Qiu; Rui Shi; Mingming Shao; Shichang Zhao; Fei Yu; Yihua Luan (Science China Earth Sciences, 2026)

Dynamic monitoring deployment for improved key-region radiological forecasts via ensemble-based forward–adjoint information - Qingyun Li; Tao He; Mingye Li; Yu Song; Junfang Zhang; Bing Lian; Liye Liu; Rui Qiu; Junli Li; Xiaole Zhang (Journal of Hazardous Materials, 2026)

Corrigendum to “Effect of magnetic field-assisted curing on NaCl diffusion, protein structure, and quality attributes of beef” [Food Res. Int. 236 (2026) 119292] - Rui-Cheng Xu; Qiu-Ya Ji; Han Tao; Bao-Cai Xu; Ran Feng; Bao Zhang (Food Research International, 2026)

Strength characteristics and correlation of red-bed soft rock in Southwest China - Enxi Qiu; Qiuling Chen; Xiaotian Xiong; Bin Wang; Xiwang Sun; Rui Zhang; Xusheng Wan; Mengfei Qu (Bulletin of Engineering Geology and the Environment, 2026)

Enhanced dimethylsulfide emissions following eutrophication remediation in a coastal bay: biogeochemical and hydrological controls - Xiao-Ran Li; Jin-Wei Wu; Xiao-Song Zhong; Hao Qiao; Shi-Bo Yan; Feng Xu; Yu-Cheng Jiang; Rui-Te Zhang; Yu-Hao Qiu; Hong-Hai Zhang (Progress in Oceanography, 2026)

Effect of magnetic field-assisted curing on NaCl diffusion, protein structure, and quality attributes of beef - Rui-Cheng Xu; Qiu-Ya Ji; Han Tao; Bao-Cai Xu; Ran Feng; Bao Zhang (Food Research International, 2026)

High-efficiency integration of capacitive deionization and electricity generation in single cycle enabled by basswood-derived free-standing carbon electrode - Yao Qiu; Rui Zhang; Shuyu Kong; Yishuo Teng; Dongling Li; Ming Hou; Jingwen Wang; Yongzhao Hou; Guangwu Wen; Dong Wang (Desalination, 2026)

Reprogrammable actuation in shape memory hydrogels with soft and hard magnetic particles - Ye Tian; Yuanyuan Bian; Zike Chen; Chang Zhao; Chengqian Zhang; Yi Song; Ye Qiu; Aiping Liu; Rui Xiao; Lu Dai; Huaping Wu (Chemical Engineering Journal, 2026)

Techno-economic assessment of offshore wind multi-path energy conversion and storage-transport: electricity, hydrogen, and methanol - Lei Pan; Yunfei Ding; Yuxuan Wang; Yi Pang; Jianwei Chen; Yanwei Jing; Haibo Qiu; Rui Gao; Liyang Zhang (Ocean Engineering, 2026)

Antimony precipitation processes of orogenic and magmatic-hydrothermal gold‑antimony systems in the West Qinling Orogen, China - Lian Zhang; Hao-Cheng Yu; Jie Wang; Rui Zhu; Lei Wang; Deng-Yang He; Jin-Hong Qiu; Jia-Hui Zhou; Kun-Feng Qiu (Chemical Geology, 2026)

Mechanical Properties of Glycated Cracked Articular Cartilage Under Uniaxial and Cyclic Tensile Loading - Li-Lan Gao; Yi Fang; Xiang-Long Lin; De-Zhao Kong; Yan-Song Tan; Rui-Xin Li; Kai Sun; Chun-Qiu Zhang; Yanliuxing Yan (Annals of Biomedical Engineering, 2026)

Minute‐Scale Adsorption of Diverse Marine Viruses Onto Clay Minerals - Lanlan Cai; Yuan Tian; Xuan Qiu; Yongle Xu; Hailiang Dong; Rui Zhang (Environmental Microbiology, 2026)
Viruses are ubiquitous biological entities with important roles in microbial mortality, genetic exchange and biogeochemical cycles. Clays, the most abundant mineral constituents on Earth, function as highly effective adsorbents for viruses, critically modulating their environmental persistence and ecological impact. However, the mechanisms and environmental drivers governing virus–clay interactions remain poorly understood. This study systematically investigates the adsorption kinetics of nine marine viruses onto a clay mineral (smectite, NAu‐2) under environmentally representative conditions. Viruses isolated from distinct hosts (heterotrophic bacteria, cyanobacteria and eukaryotic algae) and exhibiting diverse morphological features (myovirus, siphovirus, podovirus and tailless virus) were evaluated across gradients of NAu‐2/virus concentrations, pH, temperature and ionic strength. Elevated NAu‐2 concentrations (> 50 mg/L) induced rapid and near‐complete virus adsorption (90%–99%) within 1 min, while low concentrations (0.1–10 mg/L) yielded efficiencies from negligible to > 50%. Adsorption dynamics showed minimal correlation with viral morphology and instead depended on physicochemical properties. Electron microscopy revealed preferential viral localization at edge sites of NAu‐2, driven by charge heterogeneity from protonated alumina‐oxygen octahedra. These findings provide quantitative information on virus–clay interactions and offer key insights into the availability, transport and fate of viruses in the environment, paving the way for more accurate parameterization of biogeochemical cycling across ecosystems.

Muscone Exerts Rapid Antidepressant Effects Through Modulating Glutamatergic Neural Transmission in the Anterior Cingulate Cortex Against Peripheral Inflammation-induced Depression - Xiaoyun Qiu; Xiaojie Zhang; Yuanzhi Yang; Minjuan Sun; Xiaoli Da; Jiaying Liu; Rui Wang; Jingjia Liang; Xuhong Jiang; Gang Tian; Qiyuan Shan; Yu Du; et al. (Neuroscience Bulletin, 2026)

Foliar silicon application enhances rare earth element accumulation in the hyperaccumulator Phytolacca americana - Rui-Qi Zhang; Cui-Ling Huang; Ling-Xiu Zhou; Rong-Liang Qiu; Chong Liu; Antony van der Ent; Jean-Louis Morel; Wen-Shen Liu; Ye-Tao Tang (Journal of Environmental Sciences, 2026)

Biotransport and biotransformation of arsenic in earthworm tissues: Advancing vermiremediation strategies of soil contamination - Yunxiang Xu; Muyuan Wang; Yizhao Wu; Yifan Zhang; Rui Jiang; Qi Zhao; Jibao Jiang; Hao Qiu; Yinsheng Li (Chemical Engineering Journal, 2026)

Establishment of an Astronomical Time Scale and Discussion on the Sedimentary Origin of the Member 4 Glutenite, Paleogene Wenchang Formation, Enping 21 Sag, Zhu III Depression, Pearl River Mouth Basin, South China Sea - Shangfeng Zhang; Yuying Feng; Yaning Wang; Rui Han; Gaoyang Gong; Xinwei Qiu (Journal of Marine Science and Engineering, 2026)
Coarse-grained clastic systems in rift basins are often considered unfavorable for preserving continuous astronomical records. This study investigates the thick conglomeratic succession in the upper Member 4 (43.90–44.73 Ma) of the Wenchang Formation in the Enping 21 sub-sag, Yangjiang East Sag, Zhu III Depression, Pearl River Mouth Basin. Integrating cyclostratigraphy, petrography, and seismic-logging analyses, we established a high-resolution astronomical timescale (43.90–44.73 Ma) covering approximately 828 kyr. Cyclostratigraphic results indicate a highly continuous depositional record with an optimal sedimentation rate of 19.55 cm/kyr. Petrographic and geochemical evidence—including low structural maturity, dominant igneous lithic fragments, and high detrital zircon Th/U ratios—reveals a proximal volcaniclastic source, characterizing the studied interval as tephroid successions. Anomalously high GR responses and chaotic seismic facies further distinguish this succession from conventional terrigenous deposits, linked to a nearby identified magmatic body. Our results suggest that rapid accumulation of volcaniclastic flows and ash fallout, driven by proximal magmatic activity, reduced hydrodynamic reworking and facilitated the preservation of astronomical signals. This study highlights that in active lacustrine rift basins, magmatic activity significantly dictates sedimentary infill patterns by providing rapid volcaniclastic input, thereby enabling the establishment of precise chronostratigraphic frameworks even within complex, coarse-grained depositional systems.

Coupled Source-to-Sink Relationships in a Rifted Lacustrine Basin: A Case Study of the Eocene Wenchang Formation Member 6 (W6), Yangjiang East Sag, Pearl River Mouth Basin - Shangfeng Zhang; Linyuan Shi; Yaning Wang; Gaoyang Gong; Rui Han; Xinwei Qiu (Journal of Marine Science and Engineering, 2026)
The formation and spatial distribution of sedimentary systems in rift-lake basins are jointly controlled by multiple factors, including sediment supply rates from source areas, clastic sediment transport pathways, and basin geometry and intrabasinal structural configuration (e.g., accommodation zones and faults), which strongly influence the architecture of depositional systems and basin filling processes. The Wenliu Formation (Wenliu Member, Late Paleogene) of the Wenchang Group in the Enping 20/21 Depression of the Yangjiang East Sag, Pearl River Mouth Basin, developed a multi-source and multi-channel sand-transport system; however, the matching relationships and coupling mechanisms among different source areas, transport pathways, and depositional systems remain poorly understood. Based on three-dimensional seismic data, drilling, and well-log information, combined with heavy mineral assemblages and detrital zircon U–Pb age spectra, this study comprehensively investigates the source areas, paleochannel clastic sediment transport pathways, and depositional systems of the Wenliu Member, systematically establishing the source-to-sink (S2S) framework. The results indicate that sediments of the Wenliu Member were supplied from four main source areas, including the northwestern Yangchun Uplift, northeastern Enyang low uplift, and southwestern Yangjiang low uplift, with nine major paleochannel clastic sediment transport pathways identified. The different source zones show distinct variations in area, slope characteristics, and sediment supply modes, corresponding to differentiated paleochannel types and paleodrainage configurations. The study area overall exhibits a typical multi-channel convergence depositional pattern, dominated by braid-delta and fan-delta systems. The Enyang low-slope source zone generated the largest braid-delta deposits, whereas fault-transformed source zones produced fan-delta deposits adjacent to active faults and along basin-margin fault systems. Quantitative analysis further indicates that depositional-system scale is significantly correlated with source-area size, paleodrainage development, and paleochannel geometric parameters. Large depositional bodies are more likely to form when the source area exceeds ~60 km2, the paleochannel width exceeds ~1.4 km, and the cross-sectional area exceeds ~10 km2. Integrating the spatial relationships among source areas, transport pathways, and depositional systems, four source-to-sink subsystems are identified, which can be further classified into two typical depositional patterns: a long-source gentle-slope braid-delta pattern and a proximal-source rapid-accumulation fan-delta pattern. This study elucidates the coupling relationships among source areas, clastic sediment transport pathways, and depositional sinks in a multi-source rift-lake basin, providing a geological basis for predicting sedimentary systems and guiding hydrocarbon exploration in the study area.

Astronomically Constrained Palaeoclimate Reconstruction and Drivers of Organic Carbon Burial: Evidence from the Lower Eocene Wenchang Formation, Eastern Yangjiang Sag - Rui Han; Shangfeng Zhang; Xinwei Qiu; Yaning Wang; Gaoyang Gong; Chengcheng Zhang (Journal of Marine Science and Engineering, 2026)
Sub-sag 21 in the eastern Yangjiang Sag, Pearl River Mouth Basin, South China, contains a thick lacustrine source-rock interval within the lower Wenchang Formation and is a major exploration target on the northern margin of the South China Sea. However, the timing of deposition during the early to middle Eocene remains poorly constrained, and the applicability of quantitative palaeoclimate reconstruction methods in low-latitude lacustrine basins requires further evaluation. In this study, we analyzed mudstones from the lower Wenchang Formation in Well E1. Using cyclostratigraphic constraints, we applied AstroGeoFit to construct an astronomically tuned age model, and combined palynological coexistence analysis with geochemical weathering proxies and linear–regression calibration to quantitatively reconstruct and cross-validate mean annual temperature and mean annual precipitation. Within this time-calibrated framework, we further quantified organic-carbon burial to evaluate the relationship between palaeoclimate evolution and organic-matter enrichment. The AstroGeoFit results indicate that the top of the lower Wenchang Formation in Well E1 is constrained to 44.563 Ma, and that the studied succession spans 50.249–44.563 Ma. Palynological coexistence analysis identifies three palaeoclimate phases within this interval. Method evaluation shows that the temperature reconstruction based on major-element geochemistry agrees well with the pollen-based temperature record, whereas one precipitation reconstruction based on weathering proxies shows the most robust agreement and stability relative to the pollen-based precipitation record. Reconstructed mean annual temperature ranges from 10.77 to 22.20 °C, and reconstructed mean annual precipitation ranges from 1188.27 to 1871.89 mm. Correlation analyses on the tuned timescale show that precipitation is more strongly associated than temperature with organic-matter accumulation parameters, including total organic carbon and organic carbon accumulation rate, indicating that organic carbon burial in the eastern Yangjiang Sag lake basin was mainly controlled by hydrological forcing. During the Early Eocene Climatic Optimum, carbon burial in low-latitude lakes was, therefore, not a simple response to elevated temperature, but instead reflected the integrated effects of precipitation, runoff, stratification, material supply, transport, and preservation. The evolutionary sequence further suggests that early high productivity was diluted by rapid sedimentation, reducing total organic carbon; subsequent cooling, lake deepening, and strengthened stratification enhanced organic matter preservation; and finally, tectonic subsidence together with regional humidification promoted the development and long-term preservation of high-quality lacustrine source rocks.

Twelve-year organic substitution fertilization mitigates microbial nutrient limitation and enhances soil carbon pool stability in a rubber plantation - Wenxian Xu; Yingying Zhang; Wenjie Liu; Congju Zhao; Ashar Tahir; Chuan Yang; Xinwei Guo; Rui Sun; Xiangshuai Yan; Huifang Yuan; Qiu Yang; Zhixiang Wu (Plant and Soil, 2026)

Rubber-based agroforestry systems enhancing soil carbon sequestration through improved soil aggregate stability - Wenxian Xu; Wenjie Liu; Bo Song; Yingying Zhang; Ashar Tahir; Yumiao Cao; Changgeng Kuang; Xinwei Guo; Rui Sun; Xian Zhang; Qiu Yang; Zhixiang Wu (Soil and Tillage Research, 2026)

Thermal versus chemical effects of CO2 dilution on micro-mixing flame and NO emission - Dengke Chen; Chang Xing; Rongze Ma; Penghua Qiu; Yijun Zhao; Jingyu Guan; Rui Sun; Linyao Zhang; Li Liu; Zhen Cao (Fuel, 2026)

Development and initial validation of spicy food somatosensory experience scale - Huizhen Qiu; Yidan Rui; Jiaqi Jing; Yuan Gao; Jiangming Chen; Yuchen Zhang; Siwen Zhen; Xiao Gao (Food Quality and Preference, 2026)

Occurrence, fate and correlation analysis of antibiotics and antibiotic resistance genes (ARGs) in rural domestic wastewater treatment facilities - Bentuo Xu; Hongpu Zhu; Yiyang Dai; Haowen Zhang; Zhe Qian; Mengjie Pu; Fujii Tadayuki; Wenhui Qiu; Rui Sun; Min Zhao; Xiangyong Zheng (Environmental Research, 2026)

Nitrogen removal hotspot shifts and enhancement mechanisms in anaerobic/aerobic/anoxic process under cold shock - Rui Wang; Jinjin Liu; Shengjie Qiu; Qiong Zhang; Xiyao Li; Shuying Wang; Yongzhen Peng (Bioresource Technology, 2026)

Zinc finger protein ZNF638 in brown fat deteriorates type 1 diabetes via retinol binding protein 4 - Meiyao Meng; Shuang Liu; Yinzhao Zhong; Jingyi Hu; Lijun Zhu; Jin Qiu; Rui Wang; Yuan Luo; Yingwen Wang; Wenhao Zhou; Guangyu Shan; Zhenyu Du; et al. (Science Bulletin, 2026)

Enhanced degradation of microplastics by laccase under ambient conditions: Analysis of underlying molecular mechanisms - Rui Ding; Linhan Xu; Xiaoling Shan; Xinran Qiu; Ling Ding; Bin Zhang; Xujun Liang; Lingyan Zhu; Xuetao Guo (Journal of Hazardous Materials, 2026)

Ti(IV)-incorporated covalent organic frameworks for efficient dark-photocatalytic reduction of U(VI) - Li-Ling Chen; Cheng-Peng Niu; Rui Zhang; Yun-Peng Wu; Zhen-Wen Zhang; Bin Lin; Cheng-Rong Zhang; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Journal of Environmental Chemical Engineering, 2026)

Spring Arctic sea ice decline exacerbates summer extreme precipitation in central Asia and drought in northeast China - Lingzhi Zhang; Weiliang Qiu; Qianrong Ma; Li Chen; Rui Hu; Zhonghua Qian; Pengcheng Yan; Guolin Feng (Climate Dynamics, 2026)

Brominated organic compounds in leachate across China: Occurrence and molecular variations - Jing Zheng; Ji-Tao Lv; Yue Sun; Qing-Yu Liu; Qiu-Rui Zhang; Zi-Meng Wang; Xiao-Song He (Water Research, 2026)

Depth-dependent effects of vegetation restoration on soil quality in ion-adsorbed rare earth leach residues: Insights from soil functions - Heng Zhang; Xianzhen Luo; Rui Zhang; Li Zhou; Rufeng Guo; Yuanwen Kuang; Dazhi Wen; Biao Qiu; Lingling Zhang (CATENA, 2026)

Phaeovulum Molybdatiresistens sp. nov., a Molybdate-resistant Bacterium Isolated from Eutrophic Pond Water - Jianjun Song; Yuanshuo Qiu; Ke Ma; Yuelin Liu; Jia Wang; Yaqi Liu; Xiaolong Song; Kaiyue Wang; Jinhua Hu; Weidong Mu; Yanfang Zhao; Aijv Liu; et al. (Current Microbiology, 2026)

Rare earth element hyperaccumulation in vascular plants: Occurrence, mechanisms, and applications - Ruo-Rong Liu; Cui-Ling Huang; Hong-Xiang Zheng; Chong Liu; Rui-Qi Zhang; Yue Cao; Antony van der Ent; Can-Die Xie; Wen-Shen Liu; Jean Louis Morel; Catherine Sirguey; Damien Blaudez; et al. (Critical Reviews in Environmental Science and Technology, 2025)

From rolling-in to enveloping: An active gripper for efficient handling of spherical fruits in agriculture - Huanhuan Qin; Zicheng Qiu; Haoran Zhu; Rui Diao; Fengwei Che; Xingjian Gu; Yan Luo; Baohua Zhang; Mingzhou Lu (Computers and Electronics in Agriculture, 2025)

Single-atom Pt-engineered TiO₂ photoanode enabling low-charge voltage and high-efficiency neutral Zn-air batteries via photoelectrochemical enhancement - Wenliang Wang; JiangYuan Qiu; Tao Yu; Shuming Zhang; Xingwang Niu; Rui Guo; Jinsheng Li; Xuanwen Liu (Journal of Environmental Chemical Engineering, 2025)

Green catalytic degradation of antibiotics via endogenous magnetite in bottom slag from agroforestry biomass direct-fired power plants - Junnan Rui; Jinxi Wang; Xiaoyu Xiao; Genhe He; Chunxiao Chen; Zengsheng Zhang; Zhiqiang Dong; Yuping Qiu (Journal of Environmental Chemical Engineering, 2025)

Evolution of water-soluble organic aerosol composition from clean days to haze episodes in rural area of North China Plain - Chun Chen; Long Jia; Zhiqiang Zhang; Jian Gao; Yanmei Qiu; Junling Li; Rui Gao; Ping Li; Qun Zhang; Zhijie Li; Jiaxing Sun; Nan Ma; et al. (Journal of Environmental Sciences, 2025)

Self-assembling metal–polyphenol–protein nanocomplex enhancing islet graft survival and transplantation outcome - Zeqing Wang; Yixuan Zhu; Huixiang Sheng; Yang Cheng; Ying Zhang; Yifei Yang; Zhuoxun Huang; Xiaoyue Chen; Yifan Qiu; Rui Wu; Di Huang; Wenjing Gong; et al. (Chemical Engineering Journal, 2025)

Local electron structure regulation inhibits Jahn-Teller effect of Ni/Fe/Mn-based oxide cathode toward wide-temperature sodium-ion batteries - Yuhang Zhang; Shihao Li; Rui Jin; Fangyan Liu; Yi Zhang; Huiru Wang; Ziyue Qiu; Zhian Zhang (Chemical Engineering Journal, 2025)

Effect of Manure Application on Few Soil Properties and Crop Yield Under Greenhouse Cultivation-a Comprehensive Analysis - You Wu; Jiale Zhang; Wei Si; Rui Liu; Zhenxin Qiu; Jianhua Yang; Renlei Luo; Xin Lei; Weiqi Wang; Musa Ma; Xinhao Yang; Cheng Yang (Journal of Soil Science and Plant Nutrition, 2025)

Peripheral inflammation in spinocerebellar ataxia type 3: associations with genetic and clinical manifestations - Jia-Yi Zhang; Qiu-Ni Su; Han Lin; Wei Lin; Mao-Lin Cui; Zhuo-Ying Huang; Bei-Ning Ye; Ying-Xin Ye; Yi-Lin Jia; Qing-Ying Zhu; Zhi-Han Li; Min-Ting Lin; et al. (Inflammation Research, 2025)

How stomatal, mesophyll, and biochemical limitations co-limit photosynthesis: A bilevel optimization model - Rui Zhu; Tiesong Hu; Giulia Vico; Lu Zhang; Rangjian Qiu; Yingping Wang; Yong Li; Yong Liu (Agricultural and Forest Meteorology, 2025)

Comparative predictions of solute transport with hydraulic tomography in a laboratory sandbox aquifer: the importance of the injection data - Huiyang Qiu; Jie Zhang; Yuanzheng Zhang; Yang Song; Tianning Li; Bernard Konadu Amoah; Rui Hu; Yong Huang (Advances in Water Resources, 2025)

Influence of fuel side dilution on the combustion characteristics of syngas-air micro-mixing nozzles - Dengke Chen; Penghua Qiu; Chang Liu; Wentong Wang; Rui Sun; Yijun Zhao; Linyao Zhang; Li Liu; Chang Xing (Fuel, 2025)

Enhanced effects of species richness on cadmium phytoextraction across eastern China: A meta-analysis - Rufeng Guo; Xianzhen Luo; Li Zhou; Rui Zhang; Lingling Zhang; Yuanwen Kuang; Biao Qiu; Dazhi Wen (Environmental Research, 2025)

Pt/Ca bimetallic-modified N-doped carbon for selective conversion of furfural into 1,2-pentanediol - Huiyu Liu; Ying Qiu; Rui Shan; Jun Zhang; Haoran Yuan; Yong Chen (Journal of Environmental Chemical Engineering, 2025)

Nickel complex-bridging to enhance electron transport in covalent organic frameworks for efficient photocatalytic uranium reduction - Xiao-Xing Wang; Rui Zhang; Zhi-Hai Peng; Jing-Wen Gong; En-Min Hu; Cheng-Peng Niu; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2025)

Catalytic pyrolysis of polyethylene over bimetallic-modified ZSM-5: Role of alkaline sites on structure regulation, thermal behavior and aromatics production - Huiyu Liu; Ying Qiu; Rui Shan; Jun Zhang; Haoran Yuan; Yong Chen (Fuel, 2025)

Anion-tailored solvation clusters in methyl acetate electrolyte: Achieving concurrent low temperature operation and high voltage stability - Jiaxuan Feng; Zhaojun Liu; Rui Yang; Xiaochen Wu; Xiangyu Zhang; Jianwei Qiu; Xinyu Li; Ning Liu; Fei Ding; Pengchao Si (Chemical Engineering Journal, 2025)

Using Interactive Multi-Media Panorama Virtual Reality to Balance Heritage Science, Education and Conservation At Zhoukoudian, Fangshan UNESCO Global Geopark - Jun-Ting Qiu; Tong-Yu Zhang; Lixian Tian; Xin-Min Rui; Hong-Xu Mu; Liang Qiu; Long-Xin Xu (Geoheritage, 2025)

Xylem hydraulic impairment due to stronger drought stress accounts for the reduced crown vitality and growth performance of Mongolian pine trees in higher-density plantations - Xue-Wei Gong; Yi-Lei Ouyang; Yan-Yan Liu; Jin-En Zhang; Zhao-Kui Li; Hong-Li Li; Zhuo-Qun Fang; Yu Cao; De-Dong Wu; Qiu-Rui Ning; Guang-You Hao (Agricultural and Forest Meteorology, 2025)

The synergistic effects of entomopathogenic fungus Cordyceps javanica and parasitoid Tamarixia radiata in Asian citrus psyllid management - Pei-Ping Xu; Xin-Yi Chen; Jia-Rui Wang; Zi-Tong Lu; Marguerite Mukangango; Wen-Sang; Bao-Li Qiu; Li-He Zhang; Shaukat Ali (Crop Protection, 2025)

The ultrastructure of the Cretaceous feathers highlights the evolution of the feather - Jiajia Wang; Rui Qiu; Qian Chen; Di Liu; Tongbo Zhang; Ying Li; Xinjun Zhang; Baopeng Wang; Dongyu Hu; Dong Ren; Xiaolin Wang; Xiaofei Xia; et al. (Science Bulletin, 2025)

Constructing asymmetric D′-A-D" imine covalent organic frameworks to optimize exciton effect and enhance photocatalytic reduction of U(VI) - Yang-Xing He; Xiao-Juan Chen; Rui Zhang; Hao-Xuan He; Cheng-Peng Niu; Cheng-Rong Zhang; Zhi-Hai Peng; Yuan-Jun Cai; Zhen-Wen Zhang; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2025)

Flexural behavior of reinforced concrete beams subjected to natural corrosion in marine environment - Yang Liu; Wei-Ping Zhang; Chao Jiang; Feng Wu; Jun-Li Qiu; Rui-Lin Wang; Nai-Hao Zheng (Engineering Structures, 2025)

A novel bioreactor developed for the intensification of high-viscosity aerobic fermentation processes - Qian Chen; Kai Hu; Quanfei Li; Kai Yang; Chao Zhang; Weiwei Huang; Yibin Qiu; Yian Gu; Liang Sun; Peng Lei; Jian Xue; Sha Li; et al. (Chemical Engineering Journal, 2025)

Flash elimination of nano-/microplastics from complex matrices with record efficiency and sustainability - Nuan Liu; Yingxin Ji; Feng Tang; Jianxin Fu; Chuntian Qiu; Rui Wang; Zhiyang Zhang; Lingxin Chen; Guoqing Wang (Chemical Engineering Journal, 2025)

Calcium phytate cross-linked polysaccharide hydrogels for selective removal of U(VI) from tailings wastewater - Lan Lei; Rui Zhang; Rui-Xiang Bi; Zhi-Hai Peng; Xin Liu; Tie-Ying Shi; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Water Research, 2025)

Enhanced immobilization of Cd(II) by successive isomorphic substitution with Ca(II) and Mg(II) from ternary layered double hydroxides - Xiaoxian Zhang; Junnan Rui; Shuyi Yang; Rongbing Fu; Yuping Qiu (Journal of Hazardous Materials, 2025)

Multi-shank flexible implantable neural interface for long-term olfactory neuron recording toward odor perception - Qunchen Yuan; Jiale Wang; Chunlian Qin; Shunuo Shang; Haoze Xu; Fan Wu; Yong Qiu; Haoting Zhang; Rui Sun; Ping Wang; Liujing Zhuang; Hao Wan (Chemical Engineering Journal, 2025)

Tenecteplase Plus Butyphthalide for Stroke Within 4.5–6 Hours of Onset (EXIT-BT): a Phase 2 Study - Hui-Sheng Chen; Ming-Rui Chen; Yu Cui; Xin-Yu Shen; Hong Zhang; Jiang Lu; Li-Wei Zhao; Ying-Jie Duan; Jing Li; Ya-Mei Wang; Lian-Qiu Min; Li-Hong Zhao; et al. (Translational Stroke Research, 2025)

Helicobacter pylori VacA-induced gastric mucosal atrophy: a comparative analysis with other forms of atrophic gastritis - Yang-Kun Wang; Wen-Rui Chen; Ling-Yan Lu; Ying-Ying Li; Rui-Kun Qiu; Chao-Ya Zhu; Fa-Shun Zhang; Su-Nan Wang; Si-Liang Xu (Journal of Molecular Histology, 2025)

Development of a highly efficient seeding breeding system of Notopterygium incisum - Si Cheng Yao; Qiao Jia Peng; Na Su; Yuan Yuan Jiang; Jin Qiu Liao; Long Wang; Xue Xue Deng; Rui Wu Yang; Xiang Yun Chen; Li Zhang (Plant Biotechnology Reports, 2025)

Cascading environmental, phenological, and physiological influences on spatial variability of annual gross primary productivity in the Northern Hemisphere - Lang Han; Gui-Rui Yu; Zhi Chen; Qiu-Feng Wang; Xian-Jin Zhu; Wei-Kang Zhang; Tie-Jun Wang; Zhi-Feng Yan; Tian-You Zhang; Shi-Ping Chen; Hui-Min Wang; Jun-Hua Yan; et al. (Science of The Total Environment, 2025)

The curvilinear relationship between perceived stress and spicy food craving in Young females: A non-linear mediation effect of positive emotional experience of spicy food consumption - Huizhen Qiu; Yidan Rui; Yuchen Zhang; Meiqi Hu; Shuang Zheng; Nanlin Xu; Jiaqi Jing; Pengfei Han; Hong Chen; Xiao Gao (Food Quality and Preference, 2025)

Evaluating the Centre‐Periphery Hypothesis Through Genomic Phylogeographical Comparisons of Two Sister Species of Liquidambar in East Asia's Tertiary Relict Forests - Tian‐Rui Wang; Wu‐Qin Xu; Hans‐Peter Comes; Xin‐Yi Zhang; Jun Chen; Yin‐Gang Li; Ying‐Xiong Qiu (Journal of Biogeography, 2025)
Aim Understanding the spatial distribution of genetic variation within species is a central tenet in evolutionary biology and conservation biology. This study explores how historical demographic processes and/or environmental factors interact to affect contemporary genetic variation and adaptive potential, with a specific focus on testing the ‘centre‐periphery’ hypothesis (CPH). Location Subtropical China. Taxon Liquidambar. Methods We combined comparative phylogeography, landscape genomics and niche modelling to investigate the interplay between demographic history and past/current environmental factors in shaping genetic variation in Liquidambar formosana and L. acalycina , a sister pair of East Asia's Tertiary relict forests. Results In both species, core populations occupied highly suitable habitats at highest densities. Consistent with the CPH, population genetic diversity decreased, and differentiation increased, from centre to margin in L. acalycina , but not in L. formosana , likely reflecting different demographic histories and different relative contributions of geography, past (LGM) and current climates to their present‐day genetic variation. In addition, L. formosana showed higher adaptive potential to future climate change than L. acalycina . Main Conclusions This study demonstrates that differences in contemporary genetic variation and adaptability among closely related species can be explained by contrasting demographic responses to multiple geographic/climatic factors. In turn, it should also expand our understanding of the CPH, while informing future conservation efforts for these two study species.

Dynamic cause of saltwater intrusion extremes and freshwater challenges in the Changjiang Estuary in flood season of 2022 - Rui Ma; Cheng Qiu; Jianrong Zhu; Zhilin Zhang; Yiping Zhu; Lingting Kong; Lei Ding; Wei Qiu; Hui Wu (Frontiers in Marine Science, 2025)
Estuarine regions heavily rely on the supply of freshwater from rivers, which could suffer saltwater intrusion. In the late summer and autumn of 2022, the Changjiang basin experienced prolonged severe drought, resulting in the river discharge decreasing to its lowest level according to historical records. Furthermore, the Changjiang Estuary was affected successively by three typhoons in September. Saltwater intrusion extremes have occurred since early September, resulting in the Qingcaosha Reservoir, the largest estuarine reservoir in the world, being unsuitable for water intake for 98 days. This has seriously threatened the safety of the water supply in Shanghai. No such extremely severe event has occurred since salinity has been recorded in the estuary, even in the dry season. Our findings show that saltwater intrusion extremes were caused by the combined effect of extremely low river discharge and typhoons, which drove substantial landward water transport to form a horizontal estuarine circulation flowing into the North Channel and out of the South Channel. This landward net water transport overcame seaward runoff and brought highly saline water into the estuary. The extremely low river discharge is the fundamental cause for the severe saltwater intrusion, and the typhoons greatly amplified it. The surface and bottom salinities at the water intake of the Qingcaosha Reservoir were amplified 9.6 and 23.4 times by Typhoon Hinnamonr and 10.1 and 15.1 times by Typhoon Nanmadol, respectively. We reveal the dynamic cause of saltwater intrusion extremes, which is conducive for developing effective response measures for estuarine freshwater resources safety.

New insight into the role of bisphenol A on the anammox system: Oxidative stress and quorum sensing mechanisms - Yu Tian; Lingjie Liu; Chunsheng Qiu; Dong Wang; Rui Zhang; Yanmeng Bi; Shaopo Wang; Bo Zhang (Journal of Environmental Chemical Engineering, 2025)

Swertiamarin relieves radiation-induced intestinal injury by limiting DNA damage - Zhe Zhao; Dan He; Jinyu Wang; Yu Xiao; Lixin Gong; Can Tang; Haibo Peng; Xuemei Qiu; Rui Liu; Tao Zhang; Jingyi Li (Molecular and Cellular Biochemistry, 2025)

Single- and combined-heavy metals/metalloids exposures are associated with infertility in US women aged 20–44: NHANES 2013–2020 analysis - He-Bin Chi; Jia-Jia Tang; Xiao-Yuan Fan; Han-Wen Zhang; Feng Tang; Xian-Shu Lin; Bing-Rui Yang; Na Li; Jun Guo; Li-An-Sheng Wu; Qiu-Qi Huang; Yin-Yin Xia (Reproductive Toxicology, 2025)

Precise and panoramic study on the nutritional components of specific milk of goats and sheep - Xiaowei Wang; Qian Li; Qiu Zhang; Yanzhi Wu; Rui Chen; Yinggang Sun; Yuan Pan; Siyi Li; Zeying Wang (Food Chemistry, 2025)

Tauroursodeoxycholic acid targets HSP90 to promote protein homeostasis and extends healthy lifespan - Jia-Yu Liu; Yao Wang; Yue Guo; Run-Qi Zheng; Yun-Ying Wang; Yan-Yan Shen; Yan-Hong Liu; Ai-Ping Cao; Rui-Bo Wang; Bo-Yang Xie; Shuai Jiang; Qiu-Ying Han; et al. (Science China Life Sciences, 2025)

Human settlement and destructive activities disrupt the positive contribution of dust to plant biomass growth over the past 2000 years - Lin Chen; Youliang Huang; Menghan Qiu; Zhilun Li; Rui Yang; Mengjing Li; Huiling Sun; Lixiong Xiang; Shanjia Zhang; Xiaozhong Huang; Aifeng Zhou (Global and Planetary Change, 2025)

Microwave replacing traditional concentrating process to promote the synthesis of mumefural in Prunus mume extract - Teng Long Miao; Shan Qin; Xiao Hong Chen; Long Yun Chen; Yan Qing Han; Yan Li Yuan; Xin Rui; Wei Li; Qiu Qin Zhang (Food Research International, 2025)

Portable paper-based microfluidic devices with Cu1-xAgxS NPs modification for multiplex intelligent visualized detection of adrenaline and glucose simultaneously - Huan Wang; Lihua Dong; Gina Ma; Shuang Qiu; Guiye Shan; Lijia Zhao; Yu Sun; Anni Cui; Rui Zhang; Xiaojie Liu (Analytica Chimica Acta, 2025)

Organophosphate esters in vehicle interior dust from Chinese urban areas: What are the influencing factors of the occurrence? - Kaixuan Wu; Rui Chen; Yanling Qiu; Hua Zhang; Zhiliang Zhu; Daqiang Yin (Science of The Total Environment, 2024)

The inoculation of Bacillus paralicheniformis and Streptomyces thermoviolaceus enhances the lignocellulose degradation and microbial communities during spent mushroom substrate composting - Jiao Zhang; Ya-Jie Zou; Shun-Li Wang; Wei-Wei Zhang; Qing-Jun Chen; Qiu-Ying Wang; Ti-Kun Guan; Jia-Yan Zhang; Min-Rui Zhao; Guo-Qing Zhang (Environmental Research, 2024)

Multi-omics analysis of five species of milk and specific composition links within each species - Qian Li; Xiaowei Wang; Qiu Zhang; Yanzhi Wu; Rui Chen; Yinggang Sun; Yuan Pan; Siyi Li; Zeying Wang (Food Chemistry, 2024)

Structurally programmed bioderived polyimide for foldable humidity sensors with ultrafast response and recovery times - Caihong Gong; Huilong Liu; Shaoji Wu; Zhao Liu; Sutong Zheng; Yanhuang Tang; Zhiming Qiu; Rui Zhang; Yurong Yan (Chemical Engineering Journal, 2024)

Tuning local charge polarization of covalent organic frameworks for enhanced photocatalytic uranium (VI) reduction - Xiao-Xing Wang; Cheng-Rong Zhang; Rui-Xiang Bi; Zhi-Hai Peng; Hao-Xuan He; Rui Zhang; An-Min Song; Jia-Xin Qi; Xiao-Juan Chen; Xin Liu; Yuan-Jun Cai; Ru-Ping Liang; et al. (Chemical Engineering Journal, 2024)

Myo-inositol: A potential game-changer in preventing gill cell death and alleviating “gill rot” in grass carp (Ctenopharyngodon idellus) - Jie Chen; Wei-Dan Jiang; Lin Feng; Pei Wu; Yang Liu; Xiao-Wan Jin; Hong-Mei Ren; Jia-Yong Tang; Rui-Nan Zhang; Xiao-Qiu Zhou (Fish & Shellfish Immunology, 2024)

A nationwide characterization of organochlorine pesticides (OCPs) in livestock and poultry food products across China: Residual levels, origin and the associated health risks - Lu Chen; Yongzhong Qian; Xu Wang; Qi Jia; Rui Weng; Xinglian Zhang; Yun Li; Jing Qiu (Chemosphere, 2024)

The role of pantothenic acid in alleviating hypoxia-induced liver injury of sub-adult grass carp (Ctenopharyngodon idellus): Possible mechanisms and implication - Yan Xia; Xiao-Qiu Zhou; Pei Wu; Wei-Dan Jiang; Yang Liu; Jia-Yong Tang; Rui-Nan Zhang; Lu Zhang; Hai-Feng Mi; Lin Feng (Aquaculture, 2024)

Archean atmospheric sulfur stocked in the Cretaceous gold deposits - Yong-Wen Zhang; Hong-Rui Fan; Long Li; Qiu-Li Li; Hong-Wei Peng; Ya-Chun Cai; Peng Jiang; Kai Feng (Geochemistry, 2024)

Zr-decorated hyper-cross-linked polymers for highly selective upgrading of furfural to furfuryl alcohol - Ying Qiu; Huiyu Liu; Rui Shan; Wei Zhao; Junhua Zhang; Jun Zhang; Haoran Yuan (Fuel, 2024)

Pinhole-like carriers transport in spin-coating SiO2 enabling high-efficiency dopant-free Si solar cells - Jiawang Qiu; Zhongguo Zhou; Lijuan Zhang; Xiaomin Song; Sihua Zhong; Haipeng Yin; Rui Tong; Jinghong Zhang; Wenzhong Shen; Zengguang Huang (Chemical Engineering Journal, 2024)

Changing Drip Fertigation Strategy to Decrease Greenhouse Agroecosystem Soil Nitrate Residue and Improve Tomato Production in Northwest of China - You Wu; Jiale Zhang; Shicheng Yan; Wei Si; Rui Liu; Jianhua Yang; Zhenxin Qiu; Junliang Fan; Fucang Zhang (Journal of Soil Science and Plant Nutrition, 2024)

Phase I clinical trial of intracerebral injection of lentiviral-ABCD1 for the treatment of cerebral adrenoleukodystrophy - Qiu-Hong Wang; Jing Wang; Zhi-Pei Ling; Zhi-Qiang Cui; Jie Gong; Rui Zhang; Shi-Jun Li; Yang-Yang Wang; Rui Yang; De-Hui Huang; Wen He; Jing Gao; et al. (Science Bulletin, 2024)

Enhanced photocatalytic U(VI) reduction via double internal electric field in CoWO4/covalent organic frameworks p-n heterojunction - Rui-Xiang Bi; Zhi-Hai Peng; Lan Lei; Xiao-Xing Wang; Xin Liu; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2024)

Molecular-level insight into the origin-dependent adsorption fractionation of dissolved organic matter on ferrihydrite in aquatic environment: Implications for carbon sink in eutrophic lakes - Chengyu Suo; Wensi Zhao; Shasha Liu; Rui Fu; Yi Ren; Yue Qiu; Yuxin Zhang; Zhongqi He; Baoshan Xing; Fengchang Wu (Chemical Engineering Journal, 2024)

Organic-mineral colloids regulate the migration and fractionation of rare earth elements in groundwater systems impacted by ion-adsorption deposits mining in South China - Xiao-Rui Liu; Wen-Shen Liu; Miaoyue Zhang; Chao Jin; Keng-Bo Ding; Alan J.M. Baker; Rong-Liang Qiu; Ye-Tao Tang; Shi-Zhong Wang (Water Research, 2024)

Effective and food-grade detoxification of multiple mycotoxins using yeast expressed manganese peroxidases - Yang You; Yangyu Qiu; Huidong Xu; Rui He; Lili Zhang; Zhouping Wang; Yu Xia (Food Bioscience, 2024)

IL-6/STAT3 axis is hijacked by GCRV to facilitate viral replication via suppressing type Ⅰ IFN signaling - Liang Hu; Yang Xu; Qiu-Shi Zhang; Xiao-Ying Chen; Chun Li; Rui Chen; Guo-Li Hou; Zhao Lv; Tiao-Yi Xiao; Jun Zou; Hong-Quan Wang; Jun-Hua Li (Fish & Shellfish Immunology, 2024)

Charge transport properties and mechanisms of bacterial cellulose (BC)-Zinc complexes - Rui Zhao; Tianshuo Zhang; Xianglin Qiu; Ziyi Cao; Shanshan Gao; Xiaoming Song; Yue Li; Fushan Chen; Xinyi Zhou (Carbohydrate Polymers, 2024)

Epidemiology, pathogenesis, immune evasion mechanism and vaccine development of porcine Deltacoronavirus - Xueting Shan; Rui Li; Xiang Ma; Guoqiang Qiu; Yi Xiang; Xiaojun Zhang; De Wu; Lu Wang; Jianhong Zhang; Tao Wang; Weifen Li; Yun Xiang; et al. (Functional & Integrative Genomics, 2024)

New sight in arginine-improved flesh quality: Role of MRFs, cyclins, and WNT signaling in grass carp (Ctenopharyngodon idellus) - Yu-Long Ma; Xiao-Qiu Zhou; Pei Wu; Wei-Dan Jiang; Yang Liu; Hong-Mei Ren; Rui-Nan Zhang; Shu-Wei Li; Ling Tang; Lin Feng (Aquaculture, 2024)

Protein from rapeseed for food applications: Extraction, sensory quality, functional and nutritional properties - Rui Zhang; Xuelian Fang; Zisheng Feng; Ming Chen; Xiushuang Qiu; Jinmeng Sun; Muci Wu; Jingren He (Food Chemistry, 2024)

Phosphorylated covalent organic framework/graphene composites for photoelectrothermal integrated collaborative reduction of uranium - Rui Zhang; Liang Tao; Cheng-Peng Niu; Cheng-Rong Zhang; Tie-Ying Shi; Xiao-Xing Wang; Ying-Ao Wang; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2024)

Macronutrient and PFOS bioavailability manipulated by aeration-driven rhizospheric organic nanocapsular assembly - Ming Zhang; Weifeng Qiu; Rui Nie; Qiaoyun Xia; Daoyong Zhang; Xiangliang Pan (Water Research, 2024)

Viologen-based ionic conjugated mesoporous polymer as the electron conveyer for efficient polysulfide trapping and conversion - Hai-Yang Li; Zhong-Shan Li; Gang-Hao Qiu; Rou-Rou Zhang; Ya-Rui Wang; Feng Wang; Ren-Wu Huang; Xiao-Fei Liu; Shuang-Quan Zang (Science Bulletin, 2024)

Carbon reduction effects of digital financial inclusion: Evidence from the county-scale in China - Xiao Lei; Xingru Chen; Liangfeng Xu; Rui Qiu; Bin Zhang (Journal of Cleaner Production, 2024)

Core-shell MOF@COF photocatalysts for synergistic enhanced U(VI) and tetracycline cleanup through space and carrier separation - Rui-Xiang Bi; Xin Liu; Lan Lei; Zhi-Hai Peng; Xiao-Xing Wang; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

Preparation of novel Fe-containing zeolite-A for KN-R decolorization by Fenton-like reaction - Rui Qiu; Aiyin Chen; Peng Zhang; Xuejiao Tang; Cuiping Wang; Hongwen Sun (Environmental Science and Pollution Research, 2024)

Weak correlations among leaf thermal metrics, economic traits and damages under natural heatwaves - Qiu-Rui Ning; Qiang Li; Hao-Ping Zhang; Yi Jin; Xue-Wei Gong; Rui-Fang Jiao; Emily Patience Bakpa; Han Zhao; Hui Liu (Science of The Total Environment, 2024)

Leaching and evolution of anthocyanins and aroma compounds during Cabernet Sauvignon wine fermentation with whole-process skin-seed contact - Xue-Chen Yao; Hua-Lin Zhang; Xin-Rui Ma; Nong-Yu Xia; Chang-Qing Duan; Wei-Ming Yang; Qiu-Hong Pan (Food Chemistry, 2024)

Effect of konjac glucomannan with different degrees of deacetylation on the gel behavior of transglutaminase induced soybean protein isolate emulsion gels - Yuntao Wang; Hui Zhang; Qing Liang; Xiuqin Guo; Zijian Niu; Si Qiu; Wei Xu; Rui Li (Food Hydrocolloids, 2024)

Hybrid organic frameworks: Synthesis strategies and applications in photocatalytic wastewater treatment - A review - Zhaobo Wang; Hongxin Wang; Peng Shi; Jiangyuan Qiu; Rui Guo; Junhua You; Hangzhou Zhang (Chemosphere, 2024)

Soy protein isolate amyloid fibril-coated ZrO2 nanoparticles anchored in the polyurethane sponge for rapid and effective fluoride adsorption in the wide pH range - Wenjing Lu; Chunhui Zhang; Zhiwei Lin; Peidong Su; Zhaowei Qin; Xuezhi Li; Rui Wang; Yunchang Liu; Peiyao Luo; Kepeng Qiu (Journal of Environmental Chemical Engineering, 2024)

Two birds with one stone: Gold “bridging” both nanozyme and immunosensor for sensitive double-response detection of T-2 toxin - Rui Shu; Sijie Liu; Cong Zhao; Xi Lan; Yuechun Li; Jianlong Wang; Nannan Qiu; Daohong Zhang (Chemical Engineering Journal, 2024)

Problem identification and revitalization strategies for the recovery and reconstruction of traditional villages in the Ms 6.8 Luding Earthquake - Chao Huang; Jian Qiu; Chun Liu; Rui Jiang; Chuanrong Zhao; Yi Zhang (Journal of Mountain Science, 2024)

Effects of nutrients and light in aquatic habitat on the growth of Hydrocotyle vulgaris when expanded from terrestrial to aquatic habitat - Zhi-Huan Chen; Rui Zhang; Jun-Cai Xin; Zi-Han Qian; Shu-Jie Wang; Shang-Yan Qiu; Xue-Ge He; Chao Si (Aquatic Botany, 2024)

Corrosion of Q235 carbon steel induced by sulfate-reducing bacteria in groundwater: corrosion behavior, corrosion product, and microbial community structure - Wenxin Hua; Rui Sun; Xiaoyan Wang; Yunyun Zhang; Jiaxing Li; Ri Qiu; Yu Gao (Environmental Science and Pollution Research, 2023)

First report of Fusarium sacchari causing root rot of tobacco (Nicotiana tabacum L.) in China - Rui Qiu; Caihong Li; Xiaojie Li; Yingying Zhang; Chang Liu; Chenjun Li; Yuguo Chen; Jingke Bai; Min Xu; Ruifang Song; Shujun Li (Crop Protection, 2023)

Improvement of flesh quality, muscle growth and protein deposition in adult grass carp (Ctenopharyngodon idella): The role of tryptophan - Lu-Qiao Xiao; Wei-Dan Jiang; Pei Wu; Yang Liu; Hong-Mei Ren; Ling Tang; Shu-Wei Li; Cheng-Bo Zhong; Rui-Nan Zhang; Lin Feng; Xiao-Qiu Zhou (Aquaculture, 2023)

Native ApxIIA secreted by Actinobacillus pleuropneumoniae induces apoptosis in porcine alveolar macrophages dependent on concentration and acylation - Hao Tang; Rong Wang; Siqi Pang; Weiyao Han; Qiuhong Zhang; Qiong Fang; Xiabing Chen; Qi Huang; Dexin Qiu; Rui Zhou; Lu Li (Veterinary Microbiology, 2023)

Migration and adsorption of naphthalene in road-deposited sediments from stormwater runoff: Impact of the particle size - Hongze Liu; Fuguo Qiu; Mingchen Gao; Yongjian Che; Chaohong Tan; Ziyang Zhang; Rui Yan; Haiyan Li; Meipeng Jian (Science of The Total Environment, 2023)

Three new flavones from the whole plants of Cassia auriculata Linn. and their antiviral activities - Rui-Feng Xiong; Jun-Na Zheng; Qing-Yang Wu; Ning Jiang; Yuan-Sheng He; Yong-Jun Zhang; Ben-Hui Li; Wei Li; Qiu-Fen Hu; Zhen-Yuan Xia; Yin-Ke Li (Phytochemistry Letters, 2023)

Genomic and biogenic amine-reducing characterization of Lactiplantibacillus planatraum JB1 isolated from fermented dry sausage - Shan Qin; Xian Ming Zeng; Mei Jiang; Xin Rui; Wei Li; Ming Sheng Dong; Xiao Hong Chen; Qiu Qin Zhang (Food Control, 2023)

Exploring metal-free ionic covalent organic framework nanosheets as efficient OER electrocatalysts via cationic-π interactions - Rui Wang; Ziqi Zhang; Jinquan Suo; Li Liao; Leibo Li; Zhuochen Yu; Heng Zhang; Valentin Valtchev; Shilun Qiu; Qianrong Fang (Chemical Engineering Journal, 2023)

Stable precipitation isotope records of cold wave events in Eurasia - Xinrui Lin; Guofeng Zhu; Dongdong Qiu; Linlin Ye; Yuwei Liu; Longhu Chen; Jiawei Liu; Siyu Lu; Lei Wang; Kailiang Zhao; Wenhao Zhang; Rui Li; et al. (Atmospheric Research, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Efficacy and Safety of Repetitive Transcranial Magnetic Stimulation in Spinocerebellar Ataxia Type 3: a Systematic Review and Meta‑analysis of Randomized Controlled Trials - Mengqiu Qiu; Rui Wang; Yusha Shen; Zhenggang Hu; Yanbin Zhang (The Cerebellum, 2023)

New perspective into possible mechanism in growth promotion of potassium diformate (KDF) on the juvenile grass carp (Ctenopharyngodon idella) - Xue Xue; Xiao-Qiu Zhou; Pei Wu; Wei-Dan Jiang; Yang Liu; Rui-Nan Zhang; Lin Feng (Aquaculture, 2023)

A novel culture-enriched metagenomic sequencing strategy effectively guarantee the microbial safety of drinking water by uncovering the low abundance pathogens - Songzhe Fu; Yixiang Zhang; Rui Wang; Zhiguang Qiu; Weizhi Song; Qian Yang; Lixin Shen (Journal of Environmental Management, 2023)

Demethylation-Driven ligase chain reaction for simultaneously sensitive detection of m6A demethylase FTO and m1A demethylase ALKBH3 in breast cancer at Single-Molecule level - Ming-hao Liu; Qian Zhang; Wan-tong Yu; Jian-Ge Qiu; Hui-min Yuan; Chuan-rui Wang; Bing-Hua Jiang; Yan Zhang; Chun-yang Zhang (Chemical Engineering Journal, 2023)

Application of enzymatically treated Artemisia annua L. on adult grass carp (Ctenopharyngodon idella): Improved growth performance, intestinal antioxidant capacity and apical junctional complex - Qin-Qin Dai; Xiao-Qiu Zhou; Wei-Dan Jiang; Pei Wu; Yang Liu; He-Qun Shi; Lu Zhang; Hai-Feng Mi; Jia-Yong Tang; Rui-Nan Zhang; Lin Feng (Aquaculture, 2023)

Ammonia-oxidizing bacteria are the primary N2O producers in long-time tillage and fertilization of dryland calcareous soil - Ju Bai; Yang Li; Wei Zhang; Lixia Liu; Rui Wang; Zijian Qiu; Yuwang Liu; Qiuxia Meng; Qiang Zhang; Zhiping Yang; Shiqing Li; Yongliang Wang; et al. (Soil and Tillage Research, 2023)

Research on the source-detector variance reduction method based on the AIS adjoint Monte Carlo method - Yisheng Hao; Rui Qiu; Zhen Wu; Shenshen Gao; Hui Zhang; Junli Li (Annals of Nuclear Energy, 2023)

Influence of freeze–thaw cycles on mechanical properties of moraine soils - Enxi Qiu; Qiaoling He; Qiuling Chen; Xiwang Sun; Rui Zhang; Mengfei Qu; Xusheng Wan (Transportation Geotechnics, 2023)

Transcriptome Analysis of the Mouse Medial Prefrontal Cortex in a Chronic Constriction Injury Model - Qi-Min Zheng; Zi-Rui Zhou; Xin-Yu Hou; Ning Lv; Yu-Qiu Zhang; Hong Cao (NeuroMolecular Medicine, 2023)

Resolved CFD-DEM Simulation of Free Settling of Polyhedral Particles with Various Orientations: Insights Provided by Oscillation Behavior in Quiescent Liquid - Zhimin Zhang; Yuanyi Qiu; Hao Xiong; Rui Tang (Journal of Marine Science and Engineering, 2023)
Particle settling is the process by which particulates move toward the bottom of a liquid, which can affect the sediment transport and energy balance of marine systems. However, the deficiency in understanding the resolved fluid–particle interactions with complex boundaries in the settling process awaits resolution. This study employs a hybrid approach that combines computational fluid dynamics (CFD) with the discrete element method (DEM) to fully simulate the free-settling behavior of polyhedral particles in water. The accuracy of the method is verified by comparing numerical results with experimental data of ellipsoidal particle settling. Two series of tests with horizontal and vertical particle release directions are established to investigate the effects of particle shape features, such as the aspect ratio (AR) and corner (C), on the particles’ mechanical behavior and hydrodynamic characteristics. The results demonstrate that particle shape exerts a substantial influence on fluid resistance, rotational motion, and fluid disturbance throughout the settling process. The maximum velocities in vertically released cases are roughly 1.2–1.3 times greater than those in horizontally released cases. The study highlights the potency of the resolved CFD-DEM method as a robust technique for comprehending fluid–particle phenomena within the marine geotechnical engineering, including sedimentation and erosion of seabed sediments.

A new oleanane-type triterpene from Ardisia lindleyana D.Dietr and its cytotoxic activity - Zhou Tiqiang; Wei Zhenzhen; Fu Qianyu; Qiu Rui; Zhang Guangjie; Li Bin; Dong Junxing; Zeng Chengchu (Natural Product Research, 2023)

Revised magnetostratigraphy of the Linxia Basin in the northeast Tibetan Plateau, constrained by micromammalian fossils - Yan Zheng; Zhanxiang Qiu; Zhuding Qiu; Lu Li; Xiaohao Wei; Rui Zhang; Leping Yue; Tao Deng (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Synergistic effect of double Schottky potential well and oxygen vacancy for enhanced plasmonic photocatalytic U(VI) reduction - Xin Liu; Rui-Xiang Bi; Zhi-Hai Peng; Lan Lei; Cheng-Rong Zhang; Qiu-Xia Luo; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

Transcriptional investigation of the toxic mechanisms of perfluorooctane sulfonate in rats based on an RNA-Seq approach - Tianrun Wang; Xuying Zhao; Tianze Liu; Jiguang Zhang; Jing Qiu; Mei Li; Rui Weng (Chemosphere, 2023)

Low-Temperature robust MAPbI3 perovskite solar cells with power conversion efficiency exceeding 22.4% - Wenyu Qiu; Yukun Wu; Yichen Wang; Zhiting Yang; Rui Yang; Chenxi Zhang; Yang Hao; Yuying Hao (Chemical Engineering Journal, 2023)

Dissipation and movement of soil water in artificial forest in arid oasis areas: Cognition based on stable isotopes - Dongdong Qiu; Guofeng Zhu; Xinrui Lin; Yinying Jiao; Siyu Lu; Jiatong Liu; Jiawei Liu; Wenhao Zhang; Linlin Ye; Rui Li; Qinqin Wang; Longhu Chen (CATENA, 2023)

The PIWI-specific insertion module helps load longer piRNAs for translational activation essential for male fertility - Xin Wang; Di-Hang Lin; Yue Yan; An-Hui Wang; Jiaoyang Liao; Qian Meng; Wen-Qing Yang; Heng Zuo; Min-Min Hua; Fengjuan Zhang; Hongwen Zhu; Hu Zhou; et al. (Science China Life Sciences, 2023)

Three new isoquinoline alkaloids from the cigar tobacco-derived endophytic fungus Aspergillus felis - Yue-Yu Ma; Gui Pu; Xue-Ju Cha; Rui-Feng Xiong; Guang-Hai Zhang; Heng Yao; Mei-Fen Bao; Guang-Hui Kong; Yin-Ke Li; Qiu-Fen Hu; Yu-Ping Wu (Phytochemistry Letters, 2023)

Mineralogy and geochemistry of the Zedong Late Cretaceous (∼94 Ma) biotite granodiorite in the Southern Lhasa Terrane: Implications for the tectonic setting and Cu-Au mineralization - Weice Zhang; Zhidan Zhao; Dong Liu; Kunfeng Qiu; Qing Wang; Di-Cheng Zhu; Tiannan Yang; Yingchao Liu; Rui Wang; Zengqian Hou; Xuanxue Mo (Lithos, 2023)

D-π-A array structure of Bi4Ti3O12-triazine-aldehyde group benzene skeleton for enhanced photocatalytic uranium (VI) reduction - Xin Liu; Rui-Xiang Bi; Feng-Tao Yu; Cheng-Rong Zhang; Qiu-Xia Luo; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

Excited-state intramolecular proton transfer emitter for efficient violet-blue organic light-emitting diodes with hybridized local/charge transfer channel - Yibing Wu; Rongxin Wang; Rui Lin; Xuee Xu; Xingye Zhang; Osamah Alsalman; Yu Qiu; Ashraf Uddin; Xinhua Ouyang (Chemical Engineering Journal, 2023)

Wide-Scope Multi-residue analysis of pesticides in beef by gas chromatography coupled with quadrupole Orbitrap mass spectrometry - Xu Pang; Jing Qiu; Zhaoyang Zhang; Pi Li; Jiangtao Xing; Xin Su; Guiqiao Liu; Changyuan Yu; Rui Weng (Food Chemistry, 2023)

JA-induced TaMPK6 enhanced the freeze tolerance of Arabidopsis thaliana through regulation of ICE-CBF-COR module and antioxidant enzyme system - Meng-Meng Yu; Rui Wang; Jing-Qiu Xia; Chang Li; Qing-Hua Xu; Jing Cang; Yu-Ying Wang; Da Zhang (Plant Science, 2023)

Efficient removal of Cr(VI) by the modified biochar with chitosan schiff base and MnFe2O4 nanoparticles: Adsorption and mechanism analysis - Ling Yan; Weijuan Guo; Binbin Huang; Yujun Chen; Xinyu Ren; Yiyang Shen; Yefeng Zhou; Rui Cheng; Jie Zhang; Muqing Qiu; Baowei Hu (Journal of Environmental Chemical Engineering, 2023)

An in-situ strategy to construct uracil-conjugated covalent organic frameworks with tunable fluorescence/recognition characteristics for sensitive and selective Mercury(II) detection - Xi-Rui Deng; A-Wei Hu; Sheng-Qian Hu; Wen-Li Yang; Chen Sun; Sai-Jin Xiao; Gui-Ping Yang; Qiong-Qing Zheng; Ru-Ping Liang; Li Zhang; Jian-Ding Qiu (Analytica Chimica Acta, 2023)

Coupling coordination and influencing factors of urban spatial accessibility and economic spatial pattern in the New Western Land-Sea Corridor - Ting Zhang; Yuanhong Qiu; Rui Ding; Jian Yin; Yuequn Cao; Yiming Du (Environmental Science and Pollution Research, 2023)

SnS2-covalent organic framework Z-scheme van der Waals heterojunction for enhanced photocatalytic reduction of uranium (VI) in rare earth tailings wastewater - Xin Liu; Rui-Xiang Bi; Cheng-Rong Zhang; Qiu-Xia Luo; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2023)

Highly sensitive surface-enhanced Raman scattering (SERS) imaging for phenotypic diagnosis and therapeutic evaluation of breast cancer - Chonggui Qiu; Wei Zhang; Yanhong Zhou; Hongwang Cui; Yanlong Xing; Fabiao Yu; Rui Wang (Chemical Engineering Journal, 2023)

Vitellogenin accumulation leads to reproductive senescence by impairing lysosomal function - Jie Tang; Yi-Cheng Ma; Yuan-Li Chen; Rui-Qiu Yang; Heng-Chen Liu; Xin Wang; Baosen Ni; Cheng-Gang Zou; Ke-Qin Zhang (Science China Life Sciences, 2023)

Effects of social capital on farmers’ choices of climate change adaptation behavior in Dazu District, China - Lin Li; Jianjun Jin; Rui He; Foyuan Kuang; Chenyang Zhang; Xin Qiu (Climate and Development, 2023)

A national-scale distribution of organochlorine pesticides (OCPs) in cropland soils and major types of food crops in China: Co-occurrence and associated risks - Lu Chen; YongZhong Qian; Qi Jia; Rui Weng; Xinglian Zhang; Yun Li; Jing Qiu (Science of The Total Environment, 2023)

Plastome evolution and phylogenomics of Impatiens (Balsaminaceae) - He Qiu; Zhi-Hui Zhang; Mei-Zhen Wang; Xin-Jie Jin; Jie-Dong Lin; Hans Peter Comes; Jing-Xuan Chen; Rui-Ning Cui; Ru-Qing Duan; Pan Li (Planta, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Development of a recombinant adenovirus-vectored vaccine against both infectious hematopoietic necrosis virus and infectious pancreatic necrosis virus in rainbow trout (Oncorhynchus mykiss) - Shouhu Li; Xincang Li; Rui Yuan; Xiaoxue Chen; Shouxu Chen; Yu Qiu; Qingfeng Yang; Meng Wang; Jiangao Shi; Shuo Zhang (Fish & Shellfish Immunology, 2023)

Mechanism of bisphenol S exposure on color sensitivity of zebrafish larvae - Liguo Qiu; Shuhui Wei; Yixin Yang; Rui Zhang; Shaoguo Ru; Xiaona Zhang (Environmental Pollution, 2023)

Rural residents' climate change perceptions, personal experiences, and purchase intention–behavior gap in energy-saving refrigeration appliances in Southwest China - Rui He; Jianjun Jin; Xin Qiu; Chenyang Zhang; Jubo Yan (Environmental Impact Assessment Review, 2023)

All-in-one additive enables defect passivated, crystallization modulated and moisture resisted perovskite films toward efficient solar cells - Chuanming Tian; Yu Zhao; Xuefei Han; Bin Li; Yichuan Rui; Hao Xiong; Yu Qiu; Wei An; Kerui Li; Chengyi Hou; Yaogang Li; Hongzhi Wang; et al. (Chemical Engineering Journal, 2023)

Solar ring mission: Building a panorama of the Sun and inner-heliosphere - Yuming Wang; Xianyong Bai; Changyong Chen; Linjie Chen; Xin Cheng; Lei Deng; Linhua Deng; Yuanyong Deng; Li Feng; Tingyu Gou; Jingnan Guo; Yang Guo; et al. (Advances in Space Research, 2023)

Associations of exposure to lead and cadmium with risk of all-cause and cardiovascular disease mortality among patients with type 2 diabetes - Kai Zhu; Yuge Zhang; Qi Lu; Tingting Geng; Rui Li; Zhenzhen Wan; Xuena Zhang; Yujie Liu; Lin Li; Zixin Qiu; Meian He; Liegang Liu; et al. (Environmental Science and Pollution Research, 2022)

Isolation and Analysis of Reverse Transcriptase of Ty1-copia-Like Retrotransposons in Sugarcane - Jun-Xian Liu; Jing Liu; Tai-Yi Yang; Li-Min Liu; Li-Hang Qiu; Yi-Jing Gao; Wei-Xing Duan; Jing-Chao Lei; Hong-Jian Liu; Rong-Hua Zhang; Wei-Zhong He; Song Li; et al. (Sugar Tech, 2022)

Alcohol dependence inpatients classification with GLM and hierarchical clustering integration using fMRI data of alcohol multiple scenario cues - Abdulqawi Alarefi; Naji Alhusaini; Xunshi Wang; Rui Tao; Qinqin Rui; Guoqing Gao; Liangjun Pang; Bensheng Qiu; Xiaochu Zhang (Experimental Brain Research, 2022)

A Realistic and Integrated Model for Evaluating Offshore Oil Development - Rui Qiu; Zhuochao Li; Qin Zhang; Xin Yao; Shuyi Xie; Qi Liao; Bohong Wang (Journal of Marine Science and Engineering, 2022)
With the rising consumption of oil resources, major oil companies around the world have increasingly engaged in offshore oil exploration and development, and offshore oil resources have accounted for an increasing proportion. Offshore oil engineering projects are capital intensive, and the development of offshore oil fields faces a tough battle, especially in a period of low oil prices. Thus, a comprehensive evaluation model is highly needed to help assess economic benefits and provide meaningful and valuable information for operators and investors to make sensible decisions. This study firstly proposed a realistic and integrated evaluation model for offshore oil development based on actual historical project data. This evaluation model incorporated modules from the underwater system to the platform system and processes from oil reservoir extraction to oil, gas and water treatment. The uncertain parameters in the evaluation process are dealt with by sensitivity analysis and Monte Carlo simulation. The proposed model is applied to a typical offshore oil development project in Bohai Bay, China. The results reveal that the recovery factor and oil price have the greatest impact on the economic benefits. In the case of deterministic analysis, the breakeven oil price of the project is 40.59 USD/bbl. After considering the uncertainty of project parameters, the higher the oil price, the greater the probability of NPV > 0. When the oil price is higher than 70 USD/bbl, even with uncertain project parameters, the probability of NPV > 0 can still be as high as 97.39%.

The effects of dietary fermented wheat bran polysaccharides on mucosal and serum immune parameters, hepatopancreas antioxidant indicators, and immune-related gene expression of common carp (Cyprinus carpio) juveniles - Rui-Fang Wang; Yuan Wang; Jun Zhang; Mei-Qi Weng; Yu-Hui Liu; Qiu-Yan Cheng; Min Song; Yan-Ping Yang; Xiao-Ping An; Jing-Wei Qi (Aquaculture International, 2022)

Metatranscriptomic analysis of host response and vaginal microbiome of patients with severe COVID-19 - Meng Xiao; Bo Lu; Rui Ding; Xia Liu; Xian Wu; Yaqian Li; Xudong Liu; Lin Qiu; Zhibo Zhang; Jing Xie; Yu Chen; Dong Zhang; et al. (Science China Life Sciences, 2022)

Effects of dietary protein concentration on growth and anti-oxidant capacity of coho salmon Oncorhynchus kisutch (Walbaum, 1792) alevins - Cong-mei Xu; Hai-rui Yu; Qin Zhang; Ling-yao Li; Jing-jing Fan; Meng-jie Guo; Fang-hui Li; Xiang-yi Qiu; Ling-ling Shan (Aquaculture International, 2022)

Heavy metal pollution from copper smelting during the Shang Dynasty at the Laoniupo site in the Bahe River valley, Guanzhong Basin, China - Menglei Wu; Yana Jia; Yuzhu Zhang; Rui Wen; Jiahua Guo; Ninglian Wang; Wanqing Liu; Haijun Qiu; Haoyu Wang; Yiheng Xian; Chun Yu; Ting Yang (Journal of Geographical Sciences, 2021)

Systematic analysis of differentially expressed ZmMYB genes related to drought stress in maize - Peng-Yu Zhang; Xiao Qiu; Jia-Xu Fu; Guo-Rui Wang; Li Wei; Tong-Chao Wang (Physiology and Molecular Biology of Plants, 2021)

DNA Methyltransferase 1 Is Dysregulated in Parkinson’s Disease via Mediation of miR-17 - Hong-Qiu Zhang; Jian-Yong Wang; Zhao-Feng Li; Lei Cui; Shi-Shi Huang; Lan-Bing Zhu; Yue Sun; Rui Yang; Hui-Hui Fan; Xiong Zhang; Jian-Hong Zhu (Molecular Neurobiology, 2021)

Effects of Diversified Cropping Sequences and Tillage Practices on Soil Organic Carbon, Nitrogen, and Associated Fractions in the North China Plain - Ahmad Latif Virk; Wen-Sheng Liu; Jia-Rui Niu; Cheng-Tang Xu; Qiu-Yue Liu; Zheng-Rong Kan; Xin Zhao; Hai-Lin Zhang (Journal of Soil Science and Plant Nutrition, 2021)

Toonamicrocarpavarin, a new tirucallane-type triterpenoid from Toona Ciliata - Ling Zhang; Jianjun Xia; Yanqing Duan; Keyi Wei; Rui Gao; Dasan Li; Xiaomin Liu; Tiandong Zhang; Minghua Qiu (Natural Product Research, 2021)

Prevalence of Clonorchis sinensis infection in fish in South‐East Asia: A systematic review and meta‐analysis - Ying Zhang; Qing‐Long Gong; Qing‐Bo Lv; Yang‐Yuan Qiu; Yan‐Chun Wang; Hong‐Yu Qiu; Xin‐Rui Guo; Jun‐Feng Gao; Qiao‐Cheng Chang; Chun‐Ren Wang (Journal of Fish Diseases, 2020)
Clonorchis sinensis , an important fish‐borne zoonotic trematode, is widely distributed in South‐East Asia, especially in China. Infections from human and animal reservoir hosts occur due to the consumption of raw or undercooked fish with C. sinensis metacercariae. This study aimed to evaluate the prevalence of C. sinensis metacercariae in fish in South‐East Asia via systematic review and meta‐analysis. We searched PubMed, ScienceDirect, China National Knowledge Infrastructure, Wanfang and Chongqing VIP databases for studies published between 1976 and 2020 that are related to the prevalence of C. sinensis metacercariae in fish. Studies were screened with keywords based on inclusion and exclusion criteria. Seventy‐one eligible articles were identified, covering three countries: China, Korea and Vietnam. The pooled prevalence of C. sinensis metacercariae in fish from South‐East Asia was 30.5%, with 35.1% in China, 29.7% in Korea and 8.4% in Vietnam. In subgroup analyses of climate, season, water source and publication date, the highest prevalence was identified in the Dwb climate type (43.3%), summer (70.2%), river (34.5%) and pre‐2001 publications (38.9%), respectively. In comparison, the lowest prevalence was found in the Dfa climate type (14.5%), winter (19.5%), lake (8.0%) and post‐2001 publications (23.8%). Meta‐regression results indicated that country ( p = .009), the published time ( p = .035) and water source subgroups ( p = .003) may be the source of heterogeneity. Overall, our study indicates that a high prevalence of C. sinensis infections occurs in fish in China, Korea and Vietnam, illuminating a significant public health concern in these countries.

Apigetrin ameliorates streptozotocin-induced pancreatic β-cell damages via attenuating endoplasmic reticulum stress - Rui Zhang; Jie Shi; Tingting Wang; Xiaonan Qiu; Ruixia Liu; Yitian Li; Qing Gao; Ning Wang (In Vitro Cellular & Developmental Biology - Animal, 2020)

Intrusion of Fall Armyworm (Spodoptera frugiperda) in Sugarcane and Its Control by Drone in China - Xiu-Peng Song; Yong-Jian Liang; Xiao-Qiu Zhang; Zhen-Qiang Qin; Jin-Ju Wei; Yang-Rui Li; Jian-Ming Wu (Sugar Tech, 2020)

Effects of Spray Parameters of Drone on the Droplet Deposition in Sugarcane Canopy - Xiao-Qiu Zhang; Xiu-Peng Song; Yong-Jian Liang; Zhen-Qiang Qin; Bao-Qing Zhang; Jin-Ju Wei; Yang-Rui Li; Jian-Ming Wu (Sugar Tech, 2020)

Separating and imaging diffractions in dip domain on the basis of slope analysis - Xue Kong; De-Ying Wang; Zhen-Chun Li; Rui-Xiang Zhang; Qiu-Yuan Hu (Applied Geophysics, 2020)

Effect of waste compaction density on stabilization of aerobic bioreactor landfills - Zhongping Qiu; Mingxing Li; Luziping Zhang; Rui Zhao; Min Li (Environmental Science and Pollution Research, 2020)

Biological controls over the abundances of terrestrial ammonia oxidizers - Rui Xiao; Yunpeng Qiu; Jinjin Tao; Xuelin Zhang; Huaihai Chen; S. Chris Reberg‐Horton; Wei Shi; H. David Shew; Yi Zhang; Shuijin Hu (Global Ecology and Biogeography, 2020)
Aim Ammonia‐oxidizing archaea (AOA) and bacteria (AOB) are the primary agents for nitrification, converting ammonia (NH 4 + ) into nitrate (NO 3 − ) and modulating plant nitrogen (N) utilization and terrestrial N retention. However, there is still lack of a unifying framework describing the patterns of global AOA and AOB distribution. In particular, biotic interactions are rarely integrated into any of the conceptual models. Location World‐wide. Time period 2005–2016. Major taxa studied Ammonia‐oxidizing archaea and ammonia‐oxidizing bacteria. Methods A meta‐analysis and synthesis were conducted to obtain a general picture of global AOA and AOB distribution and identify the primary driving factors. A microcosm experiment was then conducted to assess effects of relative carbon to nitrogen availability for heterotrophic microbes on AOA and AOB in two distinct soils. A mesocosm experiment was further carried out to characterize the effects of plant roots and their arbuscular mycorrhizal fungi (AMF) on AOA and AOB abundances using hyphae‐ or root‐ingrowth techniques. Results Our meta‐analysis showed that soil carbon to nitrogen (C/N) ratios explained the most variance in AOA and AOB abundances, although soil pH had a significant effect. Experimental results demonstrated that high cellulose and mineral N inputs increased total microbial biomass and microbial activities, but inhibited AOA and AOB, suggesting microbial inhibition of AOA and AOB. Also, AMF and roots suppressed AOA and AOB, respectively. Main conclusions Our study provides convincing evidence illustrating that relative carbon to nitrogen availability can predominantly affect the abundances of AOA and AOB. Our experimental results further validate that biotic competition among plants, heterotrophic microbes and ammonia oxidizers for substrate N is the predominant control upon AOA and AOB abundances. Together, these findings provide new insights into the role of abiotic and biotic factors in modulating terrestrial AOA and AOB abundances and their potential applications for management of nitrification in an increasing reactive N world.

Enhancing remote sensing image retrieval using a triplet deep metric learning network - Rui Cao; Qian Zhang; Jiasong Zhu; Qing Li; Qingquan Li; Bozhi Liu; Guoping Qiu (International Journal of Remote Sensing, 2020)

Application of Multi-rotor Unmanned Aerial Vehicle Application in Management of Stem Borer (Lepidoptera) in Sugarcane - Xiao-Qiu Zhang; Yong-Jian Liang; Zhen-Qiang Qin; De-Wei Li; Chun-Yan Wei; Jin-Ju Wei; Yang-Rui Li; Xiu-Peng Song (Sugar Tech, 2019)

Impact of Seed Coating Agents on Single-Bud Seedcane Germination and Plant Growth in Commercial Sugarcane Cultivation - Yong-Jian Liang; Xiao-Qiu Zhang; Liu Yang; Xi-Hui Liu; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2019)

QsvR integrates into quorum sensing circuit to control Vibrio parahaemolyticus virulence - Yiquan Zhang; Linghui Hu; Yue Qiu; George Osei‐Adjei; Hao Tang; Ying Zhang; Rui Zhang; Xiumei Sheng; Shungao Xu; Wenhui Yang; Huiying Yang; Zhe Yin; et al. (Environmental Microbiology, 2019)
Summary Vibrio parahaemolyticus , the leading cause of seafood‐associated gastroenteritis worldwide, requires the two type‐III secretion systems (T3SS1 and T3SS2) and a thermostable direct hemolysin (encoded by tdh1 and tdh2 ) for full virulence. The tdh genes and the T3SS2 gene cluster constitute an 80 kb pathogenicity island known as Vp‐PAI located on the chromosome II. Expression of T3SS1 and Vp‐PAI is regulated in a quorum sensing (QS)‐dependent manner but its detailed mechanisms remain unknown. Herein, we show that three factors (QS regulators AphA and OpaR and an AraC‐type transcriptional regulator QsvR) form a complex regulatory network to control the expression of T3SS1 and Vp‐PAI genes. At low cell density (LCD), whereas Vp‐PAI expression is repressed, T3SS1 genes are induced by AphA, which directly binds (an operator region of) the exsBAD‐vscBCD operon. At high cell density (HCD), the bacterium turns off T3SS1 expression by replacing AphA with OpaR, triggering the induction of Vp‐PAI. Furthermore, QsvR binds to the regulatory regions of all the tested T3SS1 and Vp‐PAI genes to activate their transcription at HCD. Taken together, our data highlight how multiple QS regulators contribute to the pathogenicity of V. parahaemolyticus by precisely controlling the expression of major virulence determinants during different stages of growth.

Cloning and Identification of Differentially Expressed Genes Associated with Smut in Sugarcane - Xiu-Peng Song; Dan-Dan Tian; Ming-Hui Chen; Zhen-Qiang Qin; Jin-Ju Wei; Chun-Yan Wei; Xiao-Qiu Zhang; De-Wei Li; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2018)

Recent Developments in Commercial Processes for Refining Bio-Feedstocks to Renewable Diesel - Bo Zhang; Jinsheng Wu; Changyan Yang; Qi Qiu; Qiangu Yan; Rui Li; Baowei Wang; Jinlong Wu; Yigang Ding (BioEnergy Research, 2018)

Nature and origin of Triassic igneous activity in the Western Qinling Orogen: the Wenquan composite pluton example - Kun-Feng Qiu; Hao-Cheng Yu; Zong-Yang Gou; Zhi-Lu Liang; Jia-Lin Zhang; Rui Zhu (International Geology Review, 2018)

Diffraction separation by plane-wave prediction filtering - Xue Kong; De-Ying Wang; Zhen-Chun Li; Rui-Xiang Zhang; Qiu-Yuan Hu (Applied Geophysics, 2017)

Influence of Inoculation of Leifsonia xyli subsp. xyli on Photosynthetic Parameters and Activities of Defense Enzymes in Sugarcane - Xiao-Qiu Zhang; Yong-Jian Liang; Kai Zhu; Chao-Xing Wu; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2017)

The OPA1 Gene Mutations Are Frequent in Han Chinese Patients with Suspected Optic Neuropathy - A-Mei Zhang; Rui Bi; Qiu-Xiang Hu; Yu Fan; Qingjiong Zhang; Yong-Gang Yao (Molecular Neurobiology, 2017)

Sonic Hedgehog Signaling Affected by Promoter Hypermethylation Induces Aberrant Gli2 Expression in Spina Bifida - Xiao-Lin Lu; Li Wang; Shao-Yan Chang; Shao-Fang Shangguan; Zhen Wang; Li-Hua Wu; Ji-Zhen Zou; Ping Xiao; Rui Li; Yi-Hua Bao; Z-Y Qiu; Ting Zhang (Molecular Neurobiology, 2016)

Mitochondrial DNA Haplogroup A Decreases the Risk of Drug Addiction but Conversely Increases the Risk of HIV-1 Infection in Chinese Addicts - A-Mei Zhang; Qiu-Xiang Hu; Feng-Liang Liu; Rui Bi; Bi-Qing Yang; Wen Zhang; Hao Guo; Ian Logan; Yong-Tang Zheng; Yong-Gang Yao (Molecular Neurobiology, 2016)

A new triterpenoid saponin from Clinopodium chinense (Benth.) O. Kuntze - Biao Zeng; Guang-Da Liu; Bao-Bao Zhang; Shan-shan Wang; Rui Ma; Bei-Shan Zhong; Bai-qiu He; Yan Liang; Fei-Hua Wu (Natural Product Research, 2016)

Variation analysis of pathogenic Vibrio spp. and Pseudomonas spp. in Changhai mollusc farming waters using real-time PCR assay during 2011–2014 - Rui Liu; Limei Qiu; Xin Zhao; Huan Zhang; Lingling Wang; Zhanhui Hou; Dahai Gao; Linsheng Song (Marine Biology Research, 2016)

Validating GWAS-Identified Risk Loci for Alzheimer’s Disease in Han Chinese Populations - Hui-Zhen Wang; Rui Bi; Qiu-Xiang Hu; Qun Xiang; Chen Zhang; Deng-Feng Zhang; Wen Zhang; Xiaohong Ma; Wanjun Guo; Wei Deng; Liansheng Zhao; Peiyan Ni; et al. (Molecular Neurobiology, 2016)

Clinical and angiographic features associated with coronary collateralization in stable angina patients with chronic total occlusion - Zhen Sun; Ying Shen; Lin Lu; Rui-yan Zhang; Li-jin Pu; Qi Zhang; Zheng-kun Yang; Jian Hu; Qiu-jing Chen; Wei-feng Shen (Journal of Zhejiang University-SCIENCE B, 2013)

Inhibition of autophagy enhances anticancer effects of bevacizumab in hepatocarcinoma - Xian-ling Guo; Ding Li; Kai Sun; Jin Wang; Yan Liu; Jian-rui Song; Qiu-dong Zhao; Shan-shan Zhang; Wei-jie Deng; Xue Zhao; Meng-chao Wu; Li-xin Wei (Journal of Molecular Medicine, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Evaluation of the predatory mite Amblyseius hainanensis (Acari: Phytoseiidae) and artificial rainfall for the management of Brevipalpus obovatus (Acari: Tenuipalpidae) - Da-Rui Zheng; Guang-Hua Liu; Run-Jie Zhang; Andrew G. S. Cuthbertson; Bao-Li Qiu (Experimental and Applied Acarology, 2012)

Polymorphisms in the XPG gene and risk of gastric cancer in Chinese populations - Jing He; Li-Xin Qiu; Meng-Yun Wang; Rui-Xi Hua; Ruo-Xin Zhang; Hong-Ping Yu; Ya-Nong Wang; Meng-Hong Sun; Xiao-Yan Zhou; Ya-Jun Yang; Jiu-Cun Wang; Li Jin; et al. (Human Genetics, 2012)

Effects of Copper Exposure on Expression of Glutathione-Related Genes in Acidithiobacillus ferrooxidans - Jin-lan Xia; Shun Wu; Rui-yong Zhang; Cheng-gui Zhang; Huan He; Hong-chen Jiang; Zhen-yuan Nie; Guan-zhou Qiu (Current Microbiology, 2011)

Synthesis, Crystal Structure, Interaction with BSA and Antibacterial Activity of La(III) and Sm(III) Complexes with Enrofloxacin - Yan-Jun Wang; Rui-Ding Hu; Dong-Hua Jiang; Ping-Hua Zhang; Qiu-Yue Lin; Yun-Yun Wang (Journal of Fluorescence, 2011)

MicroRNA-17 post-transcriptionally regulates polycystic kidney disease-2 gene and promotes cell proliferation - Huan Sun; Qing-Wei Li; Xiao-Yan Lv; Jian-Zhong Ai; Qiu-Tan Yang; Jing-Jing Duan; Guo-Hui Bian; Yan Xiao; Yi-Dong Wang; Zheng Zhang; Yu-Hang Liu; Rui-Zhi Tan; et al. (Molecular Biology Reports, 2010)

Environmental controls over carbon exchange of three forest ecosystems in eastern China - GUI‐RUI YU; LEI‐MING ZHANG; XIAO‐MIN SUN; YU‐LING FU; XUE‐FA WEN; QIU‐FENG WANG; SHENG‐GONG LI; CHUAN‐YOU REN; XIA SONG; YUN‐FEN LIU; SHI‐JIE HAN; JUN‐HUA YAN (Global Change Biology, 2008)
Net ecosystem productivity (NEP) was continuously measured using the eddy covariance (EC) technique from 2003 to 2005 at three forest sites of ChinaFLUX. The forests include Changbaishan temperate mixed forest (CBS), Qianyanzhou subtropical coniferous plantation (QYZ), and Dinghushan subtropical evergreen broad‐leaved forest (DHS). They span wide ranges of temperature and precipitation and are influenced by the eastern Asian monsoon climate to varying extent. In this study, we estimated ecosystem respiration (RE) and gross ecosystem productivity (GEP). Comparison of ecosystem carbon exchange among the three forests shows that RE was mainly determined by temperature, with the forest at CBS exhibiting the highest temperature sensitivity among the three ecosystems. The RE was highly dependent on GEP across the three forests, and the ratio of RE to GEP decreased along the North–South Transect of Eastern China (NSTEC) (i.e. from the CBS to the DHS), with an average of 0.77 ± 0.06. Daily GEP was mainly influenced by temperature at CBS, whereas photosynthetic photon flux density was the dominant factor affecting the daily GEP at both QYZ and DHS. Temperature mainly determined the pattern of the interannual variations of ecosystem carbon exchange at CBS. However, water availability primarily controlled the interannual variations of ecosystem carbon exchange at QYZ. At DHS, NEP attained the highest values at the beginning of the dry seasons (autumn) rather than the rainy seasons (summer), probably because insufficient radiation and frequent fog during the rainy seasons hindered canopy photosynthesis. All the three forest ecosystems acted as a carbon sink from 2003 to 2005. The annual average values of NEP at CBS, QYZ, and DHS were 259 ± 19, 354 ± 34, and 434 ± 66 g C m −2 yr −1 , respectively. The slope of NEP that decreased with increasing latitude along the NSTEC was markedly different from that observed on the forest transect in the European continent. Long‐term flux measurements over more forest ecosystems along the NSTEC will further help verify such a difference between the European forest transect and the NSTEC and provide insights into the responses of ecosystem carbon exchange to climate change in China.

Insulin inhibits β-adrenergic action in ischemic/reperfused heart: a novel mechanism of insulin in cardioprotection - Qiu-Jun Yu; Rui Si; Ning Zhou; Hai-Feng Zhang; Wen-Yi Guo; Hai-Chang Wang; Feng Gao (Apoptosis, 2008)

Cloning, expression, and pharmacological activity of BmK AS, an active peptide from scorpion Buthus martensii Karsch - Jian-Hua Shao; Yue-Qiu Wang; Xiao-Yan Wu; Rui Jiang; Rong Zhang; Chun-Fu Wu; Jing-Hai Zhang (Biotechnology Letters, 2007)

Isolation and molecular characterization of the Triticum aestivum L. ethylene-responsive factor 1 (TaERF1) that increases multiple stress tolerance - Zhao-Shi Xu; Lan-Qin Xia; Ming Chen; Xian-Guo Cheng; Rui-Yue Zhang; Lian-Cheng Li; Yun-Xiang Zhao; Yan Lu; Zhi-Yong Ni; Li Liu; Zhi-Gang Qiu; You-Zhi Ma (Plant Molecular Biology, 2007)

Safety analysis of water resources and eco-environment in Shiyang River Basin - Ji-shi Zhang; Yong-qiu Zhang; Rui-feng Pu; Ren-sheng Chen; Zhong-shan Cheng; Ming-quan Wang (Chinese Geographical Science, 2005)

New progress of research on water cycle in atmosphere in China - Wang Guo; Jia Shao-feng; Yu Gui-rui; Xu Juan; Wang Jin-xia; Wang Qiu-feng; Ge Quan-sheng; Huang Ji-kun; Xia Jun; Li Li-fnjuan; Jin De-sheng; Dong Suo-cheng; et al. (Journal of Geographical Sciences, 2001)